1999
DOI: 10.1007/s11661-999-0234-2
|View full text |Cite
|
Sign up to set email alerts
|

Finite-element method simulation of effects of microstructure, stress state, and interface strength on flow localization and constraint development in Nb/Cr2Nb in situ composites

Abstract: The effects of volume fraction of particles, stress state, and interface strength on the yield strength, flow localization, plastic constraint, and damage development in Nb/Cr 2 Nb in situ composites were investigated by the finite-element method (FEM). The microstructure of the in situ composite was represented in terms of a unit rectangular or square cell containing Cr 2 Nb particles embedded within a solid-solution-alloy matrix. The hard particles were considered to be elastic and isotropic, while the matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This issue is exacerbated by small grain sizes, as the mean free path between two intermetallic grains is shorter, thereby increasing the amount of constraint on each α‐Mo grain. Indeed, Lin and Chan169 showed that the maximum effective plastic strain occurs within the interface between a strengthening particle and the surrounding matrix (here the grain boundaries between the harder intermetallic phases and the α‐Mo matrix). Consequently, grain boundaries will fail prematurely, lowering the toughness of the material.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue is exacerbated by small grain sizes, as the mean free path between two intermetallic grains is shorter, thereby increasing the amount of constraint on each α‐Mo grain. Indeed, Lin and Chan169 showed that the maximum effective plastic strain occurs within the interface between a strengthening particle and the surrounding matrix (here the grain boundaries between the harder intermetallic phases and the α‐Mo matrix). Consequently, grain boundaries will fail prematurely, lowering the toughness of the material.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In such a situation, the toughness of the alloy is governed by the toughness of the grain boundary, and not the toughnesses of the constituent phases. Conversely, increased interfacial strength can lead to premature failure of uncracked ligaments169 or crack penetration and transgranular cleavage instead of deflection,165 again limiting the ability of the material to be toughened extrinsically. As a result, akin to many ceramic materials,178 precise control of the concentration of grain‐boundary impurities, such oxygen and silicon which lower grain boundary strength, is vitally important for insuring enhanced damage tolerance in these alloys.…”
Section: Concluding Remarks: Optimization Of Mo‐si‐b Alloys For Stmentioning
confidence: 99%
“…This issue is exacerbated by small grain sizes, as the mean free path between two intermetallic grains is shorter increasing the amount of constraint on each a-Mo grain. Lin and Chan [48] showed that the maximum effective plastic strain occurs within the interface between a strengthening particle and the surrounding matrix (here the grain boundaries between the harder intermetallic phases and the a-Mo matrix). As a result, grain boundaries fail prematurely, lowering the toughness of the material.…”
Section: Plastic Constraintmentioning
confidence: 99%
“…In such a situation, the toughness of the alloy is governed by the toughness of the grain boundary, and not the toughnesses of the constituent phases. Conversely, increased interfacial strength can lead to premature failure of uncracked ligaments [48] or crack penetration and transgranular cleavage instead of deflection [49], again limiting the ability of the material to be toughened extrinsically. As a result, akin to many ceramic materials [50], precise control of the concentration of grain-boundary impurities, such oxygen and silicon which lower grain-boundary strength, is vitally important for insuring enhanced damage tolerance in these alloys.…”
Section: Influence Of Impuritiesmentioning
confidence: 99%
“…On the other hand, hard (Nb,Ti)Cr2 particles in the two-phase composites infiuence adversely the fracture resistance by creating a high plastic constraint in the tnicrostructure [56,57]. The plastic constraint originates frotn triaxial hydrostatic stresses induced by the hatd phases in the eotnposites [59][60][61]. The level of matrix consttaint increases with increasing volume fraetions of the hard phase.…”
Section: Fracture Toughness Of In-situ Compositesmentioning
confidence: 99%